Fisheries co-management—an institutional innovation? Lessons from South East Asia and Southern Africa - Nielsen, Jesper Raakjaer; Degnbol, Poul; Viswanathan, K. Kuperan; Ahmed, Mahfuzuddin; Hara, Mafaniso; Raja Abdullah, Nik Mustapha (Elsevier, 2004)
During the last decade the co-management concept has gained increasing acceptance as a potential way forward to improve fisheries management performance. It has, however, at the same time become increasingly evident that the co-management concept is not clearly defined and means very different things to different people. In this article, we attempt to document experience available from a recent study on fisheries co-management that has researched case studies of various implementations of co-management arrangements in coastal and freshwater fisheries in South East Asia and Southern Africa, and to present a more comprehensive understanding of co-management and to summarise the experiences with both the positive outcomes and the problems in actual implementation.